Protein-polysaccharide associative phase separation applied to obtain a linoleic acid dried ingredient - Sponton, Osvaldo Ernesto (2017)
This paper gives experimental information about the application of protein-polysaccharide associative phase separation to produce a dried ingredient (powder) of linoleic acid (LA). Powder production process consisted in: (i) LA binding to a well-characterized ovalbumin nanosized heat-induced aggregate (OVAn) to form LA-OVAn complexes in solution, (ii) polysaccharides (PS) addition to promote the associative phase separation of LA-OVAn complexes, and (iii) freeze-drying of the precipitated phase in order to obtain LA-OVAn-PS powders. For this, OVAn and anionic PS (gum Arabic -GA- and high methoxyl pectin -HMP-) mixed systems were studied at different OVAn-PS concentration ratio (ROVAn:PS) and aqueous medium pH by means of a complementary techniques set: optical density at 400 nm (as a measure of turbidity), zeta potential and biopolymer phase composition determination. Biopolymer associative phase separation process was described in terms of OVAn and PS separation yield (YOVAn and YPS, respectively) and PS content necessary to precipitate OVAn (PSp). YOVAn and PSp results suggest that ROVAn:PS 1:1 and 2:1 for OVAn-GA and OVAn-HMP systems, respectively, and pH 3.0 were the most suitable conditions to obtain LA-OVAn-PS freeze-dried powders. Powders water dispersibility and LA oxidative stability were evaluated over 13 days (expressed as non-deteriorated LA percent -LAND-). Results revealed that water dispersion behavior of LA-OVAn-HMP powder was better than LA-OVAn-GA; besides it has the highest LAND (~ 80%) at the 13 day. These experimental findings highlighted that OVAn-PS associative phase separation was a convenient strategy, besides this information could be relevant to produce a LA functional ingredient.